Automated Animal Identifiction and Detection Using Machine Learing - Vipin Chandra Sao, Shubhanshu Tiwari, Siddharth V. Pillai, Yogesh Kumar Rathore (Mathematical Statistician and Engineering Applications, 2023)
Animal detection is an application of machine learning through which we are able to detect and identify animal in an image or a video. It can provide user to tackle various animal-based problems like cattle counting, monitoring animals, preventing unwanted animal invasion like monkeys etc. In an area. In this paper, machine learning is used to create an animal detection and identification ml model that can be used in a diverse area. To train the ml model we first label the images from our data set. After labelling we provide the labelled data to a ml model for training, here yolov5 is used. After 50 epochs the model was able to achieve max f1 value of 0.98 with confidence of 0.89.